From waste to wonder: exploring the hypoglycemic and anti-oxidant properties of corn processing by−products - Yang, Xiaoqian; Wang, Yuelong; Li, Jingfeng; Tai, Yuxing; Yang, Kunping; Lv, Jingwei; Sun, Jiaming; Zhang, Hui (Frontiers in Chemistry, 2024)
Introduction: The industrial processing of corn (Zeamays L.) generates by-products such as corn silk, straw peels, and straw core, which contribute to adverse environmental impacts. Our study aimed to investigate sustainable approaches for mitigating these effects by evaluating the hypoglycemic potential and mechanisms of ethyl acetate fractions derived from these corn derivatives. Methods: We employed glucose consumption assays, high glucose stress tests, UPLC-QE-Orbitrap-MS analysis, molecular docking, and simulations to assess their components and efficacy. Antioxidant capacities were evaluated using DPPH, FRAP, ABTS, and •OH scavenging assays. Results: Notably, the ethyl acetate fraction extracted from straw peels (SPE) exhibited a high concentration of flavonoids and phenolic compounds along with pronounced hypoglycemic activity and antioxidant capacity. SPE significantly enhanced glucose consumption in insulin-resistant HepG2 cells while protecting HUVECs against damage caused by high glucose levels. Molecular docking analyses confirmed the interaction between active compounds and α-glucosidase as well as α-amylase, while molecular dynamic simulations indicated stability at their binding sites. Discussion: In conclusion, the hypoglycemic and antioxidative properties observed in corn by-products such as straw peels, corn silk, and straw core can be attributed to the inhibition of α-glucosidase and α-amylase activities, coupled with their rich phenolic and flavonoid content. These findings highlight the potential of these by-products for applications in healthcare management and their sustainable utilization, demonstrating significant value in the use of agricultural residues.